2021
DOI: 10.3390/jcm10132885
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence, Clinical Characteristics and Management of Inflammatory Bowel Disease in Spain: Large-Scale Epidemiological Study

Abstract: (1) Aims: To assess the incidence of inflammatory bowel disease (IBD) in Spain, to describe the main epidemiological and clinical characteristics at diagnosis and the evolution of the disease, and to explore the use of drug treatments. (2) Methods: Prospective, population-based nationwide registry. Adult patients diagnosed with IBD—Crohn’s disease (CD), ulcerative colitis (UC) or IBD unclassified (IBD-U)—during 2017 in Spain were included and were followed-up for 1 year. (3) Results: We identified 3611 inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 29 publications
3
18
0
2
Order By: Relevance
“…In our study, the North region presented the highest IBD incidence during the whole analyzed period (Figure 5 ). This tendency became more notorious with time and seemed to agree with that registered in Spain, where the cumulative incidence of IBD in 2017 was higher in the Central and North regions of the country ( 17 ). We anticipate that this predisposition might be related to the genetic heritage of the northern populations that partially results from movements entering the Iberian Peninsula from Northern and Central Europe in the Iron Age ( 19 ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our study, the North region presented the highest IBD incidence during the whole analyzed period (Figure 5 ). This tendency became more notorious with time and seemed to agree with that registered in Spain, where the cumulative incidence of IBD in 2017 was higher in the Central and North regions of the country ( 17 ). We anticipate that this predisposition might be related to the genetic heritage of the northern populations that partially results from movements entering the Iberian Peninsula from Northern and Central Europe in the Iron Age ( 19 ).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the average incidence between 2017 and 2019 (20 cases/1,000 person-year) can be considered high and is in line with the numbers registered in other European countries (17).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These data are in the upper limit of the wide range of incidence previously described [10,14,28], ranging from 0.95 [29] to 100 per 1000 [15]. The universal access to health care within the National Health System in Spain (less than 3% of IBD patients with private insurance never use public services [30]) and the adherence of most centres to the nationwide certification programme in IBD [26] provide homogeneity to the cohort, minimizing potential bias in the clinical characteristics. We did not calculate the comparative incidence of COVID-19 between the IBD cohort and data obtained from the general population because the identification of cases did not use the same methodology.…”
Section: Discussionmentioning
confidence: 78%
“…A substantial proportion of patients with CD and IBD in general require hospitalization or surgery during their lifetime. A large-scale nation-wide study conducted by Chaparro et al in Spain showed high cumulative incidences of IBD (16.2%), corresponding with reports in northern Europe [ 5 ]. This study demonstrated higher rates of medical therapies and surgical interventions as well as significantly higher hospitalization rates among patients with CD compared to patients with UC.…”
mentioning
confidence: 66%